The effect of whole brain teaching approach on learning experiences, perceived ability and motivation towards the learning of English language among college students/ Priscilla Lawrence Avit - Lawrence Avit, Priscilla (2018)
This aim of this study is to investigate the effects of Whole Brain Teaching (WBT) approach on selected college students’ learning experiences, perceived abilities and motivation towards the learning of English language. Whole Brain Teaching (WBT) approach is a new, creative, fun and interactive approach to use in any educational settings. This study involved three phases of a mix-method approach utilizing both the quantitative and qualitative methodology. In the first phase using a descriptive design, 930 students were involved in gathering data relating to students previous language learning experiences, perceived abilities, and motivation in a classroom setting. The second phase utilizing an experimental design, namely quasi-experimental, investigated the effects of WBT approach on language learning (comprising experiences, perceived ability, and motivation) of 48 students from the experimental group and 42 students from the control group. The treatment of WBT was carried out for 12 weeks where experimental group was exposed to WBT approach while the control group was taught using the ‘normal’ classroom approach. In the final phase, purposive sampling technique was used to select the experimental group and control group of students where they were interviewed to examine their perspectives and insights of the approaches used to learn English. The first phase of the findings indicates that college students have a moderate level of language learning experiences towards English language, perceived language abilities, and motivation. Despite both groups’ show increment and positive results but the experimental group of students posted more positive language learning experiences, and a significant improvement in their perceived language abilities as well as higher motivation to learn English as a result of the WBT intervention. Therefore, this study highlights the effectiveness of the WBT approach as a means of enhancing English language teaching and learning.